Sistema de gestión en salud ocupacional: reto para los administradores del sector salud en Córdoba - Colombia (2016)
This research aims to evaluate the safety management systems and occupational health (SGSSO) in State Social Enterprises of medium complexity in Cordoba (Col). This is a descriptive study, cross with a quantitative approach. The data collection was performed taking into account the requirements of OHSAS 18001 and the regulations in force; these were processed using SPSS version 20. The results show that managers do not invest in the Integrated Management System Occupational Health and Safety, these systems are still in early stage, there is no association of the elements that comprise it and deficiencies. In addition, human capital does not have a culture of prevention in occupational safety, the above goes against public policies governing this system.